Clustering Sleep Patterns and Health Metrics Using K-Means Algorithm to Identify Profiles of Sleep Quality and Well-being in a Diverse Population - Septiadi, Abednego; Prasetyo, Muhamad Awiet Wiedanto (Bright Institute, 2025)
Sleep quality is a critical element of overall health that has garnered significant attention in recent years, particularly regarding its severe impacts on both physical and mental well-being. A growing body of research underscores that insufficient or poor-quality sleep is associated with various adverse health outcomes, ranging from cognitive impairments to chronic diseases. Studies have demonstrated that the duration and quality of sleep are intricately linked to physical, social, and emotional health outcomes among various populations, including adults and children (Lallukka et al., 2018). The crucial role sleep plays in regulating both physiological and psychological processes makes it an indispensable component of health maintenance. Research indicates that sleep disturbances can impede cognitive development in children, with implications for their growth and emotional regulation (Purwanti et al., 2024). For instance, infants who achieve a higher quality of sleep demonstrate improved cognitive abilities, which can lead to better academic performance and emotional health throughout their lives (Purwanti et al., 2024). These findings suggest that interventions designed to enhance sleep quality during infancy could yield substantial long-term health benefits. Furthermore, comparable patterns have been observed in adults, where good sleep quality significantly influences psychological factors such as emotion regulation and overall mental health (Scott et al., 2021). The psychological ramifications of poor sleep quality extend beyond mere cognitive performance. Poor sleep has been linked to increased rates of anxiety, depression, and other mood disorders (Becerra et al., 2022). A meta-analysis revealed that improving sleep quality could ameliorate the symptoms of these mental health conditions (Scott et al., 2021). Moreover, chronic sleep deprivation has been identified as a precursor to substance use disorders, suggesting a complex interplay between sleep, addiction, and mental health (Freeman & Gottfredson, 2018). The challenges of maintaining sleep quality have been exacerbated by external stressors such as the COVID-19 pandemic, leading to increased anxiety and altered sleep patterns among various demographics, particularly students and healthcare workers (Fan et al., 2021). Physical health is equally affected by sleep quality. Quality sleep is pivotal for metabolic regulation, immune function, and recovery from injuries. Poor sleep has been associated with a range of chronic health issues, including obesity, diabetes, and cardiovascular diseases (Du et al., 2021). For instance, individuals who experience poor sleep tend to exhibit higher dietary risks and poor lifestyle choices, leading to serious health complications (Du et al., 2021). The immunological impacts of sleep deprivation further elucidate its role in health, indicating that compromised sleep can weaken the immune system and elevate susceptibility to viral infections such as COVID-19 (Pillay et al., 2020).